(untitled) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2022)
Background: Enterococcus faecalis is one of the most pathogenic bacteria that causes severe infections and antibiotic resistance diseases that are related to many animals such as reptiles, insects, birds, mammals and humans. Enterococcus faecalis is considered a cytolysin bacteria that has ability to lysis blood, as it was isolated from many pathological samples such as teeth caries and intestinal samples that include urine and feces. In this article, we discuss many general characteristics of bacteria such as phenotypic and microscopic characteristics, genetic structure, virulence factors, pathogenicity, transmission, and immunity against bacteria.. Conclusion: Diseases related to intestinal infections are very important because of their impact on human health and that enterococci are part of the gut microbiome. Researchers and doctors have found that patients with ulcerative colitis and Crohn’s disease have more enterococci in their intestines compared to healthy people, where researchers have suggested that the reason as changes occur in the gut wall that enable bacteria to access and obtain food, which in turn encourages them to grow properly. The rapid development of E. faecalis strains, which made them more resistant to antibiotics, confirms the need to making several studies that help in understanding the morphological, biochemical and physiological characteristics of these bacteria. in addition to its development and classification throughout history.